Preparation and Characterization of Co(II), Ni(II),Cu(II) and Zn(II) Complexes with Unsymmetrical Tetradentate Schiff Bases Ligands - K.Sh. AL-nama; E.M. AL Nidaa (College of Education for Pure Sciences, 2019)
Complexes of  Co(II), Ni(II),Cu(II) and Zn(II) with unsymmetrical tetradentate schiff bases ligands H2L1 =2-(1Z)- (8-(2-hydroxy benzylidene amino)naphthalen-1-ylimino) methyl) -6- methoxy phenol, H2L2 =2-((E) -1-(8-(Z)-2- hydroxyl benzylidene amino) naphthalen -1- ylimino) ethyl) phenol and H2L3= 1-((8-((Z) -2-hydroxy benzylidene amino) naphthalen -1- ylimino) methyl) naphthalene-2-ol, have been prepared in (1:1) (L: M) molar ratio and characterized by elemental analysis, molar conductance, spectral method (I.R, electronic, 1H-NMR), magnetic measurements and metal content analysis. The spectral data suggest that the ligands  behave as a dibasic  tetradentate ligands with ONNO donor, and coordinate with the metal ion to form mononuclear complexes via the oxygen and nitrogen atoms of the phenolic  group and azomethine group  respectively. Conductivity data in DMF solution showed that all complexes are non-electrolyte. Magnetic moment and electronic spectra data suggested square planar geometry for all complexes .